2019
DOI: 10.1016/j.japh.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a community pharmacy transitions-of-care program on 30-day readmission

Abstract: Objectives-The primary objective of this study was to evaluate the impact of a Transitions of Care (TOC) program on both all-cause and related 30-day hospital readmission. The secondary objective was to evaluate which patient-specific factors, if any, are predictive of 30-day hospital readmission.Design, setting and participants-A transitions of care program in an outpatient pharmacy, driven primarily by student pharmacists, provided telephonic counseling to recently discharged patients. The calls were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Comer et al found that a program similar to our intervention delivered at a large health system significantly reduced 30‐day readmissions by 16% (OR 0.84; 95% CI 0.75‐0.93) among a population of 6057 intervention patients compared with 12 114 controls . Similarly, Shaver et al found a 67% decreased odds of all‐cause 30‐day readmissions (OR 0.33, 95% CI 0.22‐0.48) in their transitions of care program that included “meds‐to‐beds” as a component of the intervention . On the other hand, Lam and colleagues found that a “meds‐to‐beds” program was not independently associated with lower 30‐day readmissions (adjusted OR 0.91, 95% CI 0.79‐1.04) in a large retrospective cohort study in a tertiary care hospital .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Comer et al found that a program similar to our intervention delivered at a large health system significantly reduced 30‐day readmissions by 16% (OR 0.84; 95% CI 0.75‐0.93) among a population of 6057 intervention patients compared with 12 114 controls . Similarly, Shaver et al found a 67% decreased odds of all‐cause 30‐day readmissions (OR 0.33, 95% CI 0.22‐0.48) in their transitions of care program that included “meds‐to‐beds” as a component of the intervention . On the other hand, Lam and colleagues found that a “meds‐to‐beds” program was not independently associated with lower 30‐day readmissions (adjusted OR 0.91, 95% CI 0.79‐1.04) in a large retrospective cohort study in a tertiary care hospital .…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, while the Lam study did not include a LACE score, the intervention group in our study had significantly fewer prior hospitalizations and less comorbidities than the control group. On the other hand, in the study by Shaver and colleagues, 55% of patients in the intervention group had a LACE score of 10 of greater, suggesting a higher overall risk for readmissions among their population …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Follow‐ups can provide a bridge from one care setting or provider to the next, an opportunity for clinical pharmacists to check that the patient is following the care plan conveyed at the time of discharge and triage any difficulties during the patient's care transition. These activities can be flexible as far as when, where, and who is providing the follow‐up contact and can incorporate CMM principles to identify, resolve, and prevent medication‐related problems . If timed appropriately, follow‐up activities by clinical pharmacists can support requirements for transitional care management (TCM) billing as part of a collaborative care team …”
Section: Clinical Pharmacists’ Roles In Tocmentioning
confidence: 99%
“…These activities can be flexible as far as when, where, and who is providing the follow-up contact and can incorporate CMM principles to identify, resolve, and prevent medication-related problems. [17][18][19] If timed appropriately, follow-up activities by clinical pharmacists can support requirements for transitional care management (TCM) billing as part of a collaborative care team. [20][21][22] Interventions that focus on medication cost and acquisition can also reduce medication errors and readmissions.…”
Section: Clinical Pharmacists' Roles In Tocmentioning
confidence: 99%